PERANCANGAN MEDIA EDUKATIF TEMATIK PEKERJAAN UNTUK SISWI TK B BINTANG TIMUR BALI - Devanny Gumulya (LPPM Institut Desain dan Bisnis Bali, 2022)
There are several obstacles to online learning, which has been going on for two years due to the situation of large-scale social restrictions caused by the COVID-19 pandemic. TK Bintang Timur is a Paud Kindergarten in Bali that resumed face-to-face meetings in January. According to the findings of the interview, students become unfocused and unenthusiastic when they return to face-to-face after being online for two years. One of the solutions that can be offered to increase student focus is to create educational media that includes a collection of teaching materials as well as tools such as props, text, diagrams, photos, graphics, and videos. The learning kit theme is occupations for language, creativity, and math lessons. PKM produces two sets of educational media that teach children about various professions in demand today, ranging from YouTubers to photographers. Both sets of educational media were sent to Bali, where they received positive feedback from both teachers and the headmaster of TK Bintang Timur.